Seleção de genes cry de Bacillus thuringiensis que codificam proteínas tóxicas a insetos-praga da cultura do arroz - Pinto, Laura Massochin Nunes (Universidade do Vale do Rio do Sinos, 2002)
This work, which is part of the Preservation and Management of Ecossystems and Wild Life research line, has as its aim the selection of the Bacillus thuringiensis cry genes that codify delta-endotoxins active against rice pest insects, representatives of the Lepidoptera (Spodoptera frugiperda, Noctuidae), Coleoptera (Oryzophagus oryzae, Curculionidae) and Hymenoptera (Acromyrmex lundi, Formicidae) orders, which can be used for the management of those insect populations. In order to select B. thuringiensis active against S. frugiperda and O. oryzae there have been used isolates from soil samples that had been collected in agricultural areas in Rio Grande do Sul, and they had gone through the prediction of insecticidal activity by the Polimerase Chain Reaction (PCR), with the primers that magnify DNA fragments which correspond to lepidopterans-specific cry1, cry2 and cry9 genes and coleopterans-specific cry3, cry7 and cry8 genes. The preselected isolates during this phasis of the research, have been assessed re
Screening of bacillus thuringiensis cry genes which codify toxic proteins to the insects pest of rice-crop
Keywords: bacillos; coleoptera; thuringiensis; entomologia; controle biológico; agricultura; arroz; praga; lepidoptero; zoologia; coleoptero; himenoptero; lepdoptera; Ciências Biológicas